2015
DOI: 10.5430/jnep.v6n4p92
|View full text |Cite
|
Sign up to set email alerts
|

Infertility profile, psychological ramifications and reproductive tract infection among infertile women, in northern upper Egypt

Abstract: Background and objective: Reproductive tract infections (RTI) can have serious consequences, such as miscarriage and infertility. Infertility is a growing universal phenomenon, "crossed nearly all cultures and societies almost all over the World", that has a tremendous impact on women's quality of life and their psychological well-being. This is due to various stress and anxiety factors experienced by them at each stage of their life. To decrease and prevent developing psychological distress the psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 32 publications
4
39
1
Order By: Relevance
“…These resolutions were confirmed by the fourth world conference (1995) which denoted that statistics or so women and poverty were all too familiar, where women were the majority of 1.3 billion people surviving in extreme poverty. (25) This was in accordance with Ell K., et al, (2008) who reported that, Hispanics with cancer are reported to go through significant cost barriers and out-of-pocket costs and low-income women needing cancer screening follow-up report rates of cost worry up to 41%. Economic stress is also associated with depression, with higher prevalence among low-income populations, with evidence that financial strain and employment are causally related to depression.…”
Section: Statistical Data Analysissupporting
confidence: 76%
See 3 more Smart Citations
“…These resolutions were confirmed by the fourth world conference (1995) which denoted that statistics or so women and poverty were all too familiar, where women were the majority of 1.3 billion people surviving in extreme poverty. (25) This was in accordance with Ell K., et al, (2008) who reported that, Hispanics with cancer are reported to go through significant cost barriers and out-of-pocket costs and low-income women needing cancer screening follow-up report rates of cost worry up to 41%. Economic stress is also associated with depression, with higher prevalence among low-income populations, with evidence that financial strain and employment are causally related to depression.…”
Section: Statistical Data Analysissupporting
confidence: 76%
“…(56,57) It was contradicted what other researchers found which found that the rate of psychological disorder was higher among working women. (25,58) Financial strain or headache is potential to be prevalent among low-income and minority survivors, thus far the shock of economic strain on low-income survivors' disparities in cancer quality of life (QOL) outcomes remains largely undiscovered. The findings of the present survey showed that more than one half (54.5%) of the study sample didn't have adequate family income, while merely 1% of them had enough family income and can save from it.…”
Section: Statistical Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…[26][27][28] Various situations and conditions can increase the frequency and severity of the anxiety and pregnancy can often amplify this anxiety. [29] Some women are worried about whether their babies are healthy (previous pregnancy losses or fertility problems can make this an especially overriding worry). Anxiety during pregnancy may be associated with a variety of adverse consequences in terms of obstetric complications and pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%